Factors Influencing the Southeast Sulawesi Provincial Government's Infrastructure Planning and Budgeting Policies During the Covid-19 Pandemic - Nini Aryanti; Syamsunasir Syamsunasir; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
The Covid-19 pandemic has been declared a non-natural national disaster. The Southeast Sulawesi Provincial Government has made efforts to deal with Covid-19, namely by carrying out refocusing activities. Therefore, this study aims to analyze the factors that influence the infrastructure planning and budgeting policies of the Southeast Sulawesi Provincial Government during the Covid-19 pandemic. This research uses a descriptive qualitative method with a case study approach in the Provincial Government of Southeast Sulawesi. The results of this study found that the factors that influenced the implementation of planning and budgeting policies during the Covid-19 pandemic in Southeast Sulawesi Province are the poor communication within the organization of the Southeast Sulawesi Provincial Government, human resources in implementing policies, and the limited budget. From this study it was concluded that good communication had not been established within the Southeast Sulawesi Provincial Government organization, there were limitations in terms of implementers in the Southeast Sulawesi Provincial Government and resources in planning and budgeting during the Covid-19 pandemic, a limited budget, so they have to make choices about priority programs and activities and have not yet created a special planning and budgeting team during the Covid-19 pandemic.